Seamus Heaney - Vendler, Helen 1933- (Cambridge, Mass. Harvard University Press, 1998)
Helen Vendler traces Heaney's invention as it evolves from his beginnings in Death of a Naturalist (1966) through his most recent volume, The Spirit Level (1996). In sections entitled "Second Thoughts," she considers an often neglected but crucial part of Heaney's evolving talent: self-revision. Here we see how later poems return to the themes or genres of the earlier volumes, and reconceive them in light of the poet's later attitudes or techniques Vendler surveys all of Heaney's efforts in the classical forms - elegy, genre-scene, sonnet, parable, confessional poem, poem of perception - and brings to light his aesthetic and moral attitudes.
1. Anonymities: Death of a Naturalist, Door into the Dark, Wintering Out -- 2. Archaeologies: North -- 3. Anthropologies: Field Work -- 4. Alterities and Alter Egos: From Death of a Naturalist to Station Island -- 5. Allegories: The Haw Lantern -- 6. Airiness: Seeing Things -- 7. An Afterwards: The Spirit Level.
Includes bibliographical references (pages 181-183) and index
Keywords: Heaney, Seamus -- 1939-2013 -- Criticism and interpretation; Biography and autobiography--literary.; Northern Ireland -- In literature